2017
DOI: 10.1002/ange.201701789
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Stereoselective 1,4‐Addition Reactions Using CsF on Alumina as a Solid Base: Continuous‐Flow Synthesis of Glutamic Acid Derivatives

Abstract: A novel methodology using CsF⋅Al2O3 as a highly efficient, environmentally benign, and reusable solid‐base catalyst was developed to synthesize glutamic acid derivatives by stereoselective 1,4‐addition of glycine derivatives to α,β‐unsaturated esters. CsF⋅Al2O3 showed not only great selectivity toward 1,4‐addtion reactions by suppressing the undesired formation of pyrrolidine derivations by [3+2] cycloadditions, but also offered high yields for the 1,4‐adduct with excellent anti diastereoselectivities. The cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 49 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…It can be concluded that the acidic sites in FMOF-IBCIL are mainly imidazole ring and benzene ring from IBCIL and exposed open Cr(III) sites, 44 while the basic sites in FMOF-IBCIL are mainly Cl À . 45 The active sites in FMOF-IBCIL were further observed by using in-situ FT-IR spectroscopy for CO 2 adsorption with the assistance of DFT calculation. In the in-situ FT-IR spectra of CO 2 adsorption on FMOF-IBCIL, the ν 3 antisymmetric stretching band of CO 2 at 2359 cm À1 with four large shoulder peaks (2343, 2330, 2323, 2313 cm À1 ) can be observed (Figure 2A).…”
Section: De Novo Assembly Of Flp Bearing Mofsmentioning
confidence: 99%
“…It can be concluded that the acidic sites in FMOF-IBCIL are mainly imidazole ring and benzene ring from IBCIL and exposed open Cr(III) sites, 44 while the basic sites in FMOF-IBCIL are mainly Cl À . 45 The active sites in FMOF-IBCIL were further observed by using in-situ FT-IR spectroscopy for CO 2 adsorption with the assistance of DFT calculation. In the in-situ FT-IR spectra of CO 2 adsorption on FMOF-IBCIL, the ν 3 antisymmetric stretching band of CO 2 at 2359 cm À1 with four large shoulder peaks (2343, 2330, 2323, 2313 cm À1 ) can be observed (Figure 2A).…”
Section: De Novo Assembly Of Flp Bearing Mofsmentioning
confidence: 99%